2015
DOI: 10.1161/strokeaha.115.009995
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Implications of Apixaban Versus Aspirin in the Low-Risk Nonvalvular Atrial Fibrillation Patients

Abstract: Background and Purpose-Although recommended by guidelines, the benefits of treating patients with atrial fibrillation with a low-stroke risk score, with aspirin or anticoagulants, have not been clearly established. With advent of safer nonvitamin K antagonist oral anticoagulant, we assessed the clinical and economic implications of 5 mg BID of apixaban versus aspirin among patients with a relative low risk of stroke as assessed using the CHADS 2 (congestive heart failure, hypertension, age>75, diabetes mellitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…There is little evidence in previous literature on the cost-effectiveness of DOACs in AF patients with intermediate stroke risk, and only a few investigated the cost-effectiveness of DOACs compared with warfarin while considering stroke risk ( 9 , 17 , 18 ). A UK study, which included 1,000 AF patients, showed that apixaban was more cost-effective than aspirin among AF patients with intermediate stroke risk, both having an ICER of $26,852 for a CHADS score of 1 and $14,001 for a CHA 2 DS 2 -VASc score of 1, respectively ( 17 ). However, our study included 7,954 AF patients with intermediate stroke risk, and the ICER of apixaban was $8,426.71 per QALY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence in previous literature on the cost-effectiveness of DOACs in AF patients with intermediate stroke risk, and only a few investigated the cost-effectiveness of DOACs compared with warfarin while considering stroke risk ( 9 , 17 , 18 ). A UK study, which included 1,000 AF patients, showed that apixaban was more cost-effective than aspirin among AF patients with intermediate stroke risk, both having an ICER of $26,852 for a CHADS score of 1 and $14,001 for a CHA 2 DS 2 -VASc score of 1, respectively ( 17 ). However, our study included 7,954 AF patients with intermediate stroke risk, and the ICER of apixaban was $8,426.71 per QALY.…”
Section: Discussionmentioning
confidence: 99%
“…However, this reimbursement scheme is limited to AF patients with high stroke risk (defined as a CHA 2 DS 2 -VASc score of 2 or higher), as most previous studies on the cost-effectiveness of DOACs included AF patients with high stroke risk or did not consider the risk of stroke ( 16 ). Some studies have investigated the cost-effectiveness of DOACs after a stratification on individuals regarding stroke risk ( 9 , 17 , 18 ). To the best of our knowledge, no purposely designed study has investigated the cost-effectiveness of DOACs by focusing on the intermediate stroke risk group.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline estimates of the annual clinical event rates for the SOC strategy (Table 1 ) were obtained from the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE) trial [ 19 ]. Those for the PM strategy, low and intermediate-untreated risk groups (Tables 2 , 3 ) were obtained from published studies in low-risk and/or untreated or non-anticoagulated patients [ 24 , 25 ]. The clinical event rates for the intermediate-treated and high-risk groups (Tables 4 , 5 ) were obtained from the ABC-Stroke [ 17 ] and ABC-Bleeding [ 16 ] risk score data, except for ischemic and hemorrhagic stroke, MI, and death, which were derived from the hs-TnI substudy [ 26 ].…”
Section: Methodsmentioning
confidence: 99%